Acceleration towards clean energy with the emergence of promising signs of shallow geothermal resources in Northwestern Iran - Saeed Aftab; Rasoul Hamidzadeh Moghadam; Ali Kadkhodaie (Scientific Reports)
Abstract Geoenergy refers to the energy stored or generated beneath the Earth’s surface, including geothermal heat, fuels and nuclear power. Shallow geothermal resources are an excellent energy source for various applications: they are highly efficient and cost-effective, and they can heat and cool buildings, provide hot water and even generate electricity. One promising approach to detecting geothermal energy is Geographic Information System (GIS) technology. By integrating geological surveys, geophysical and geochemical measurements and remote-sensing data into a single platform, a comprehensive view of subsurface conditions can be gained. In this study, we examined the Marand region in East Azerbaijan Province to explore shallow geothermal resources. Geochemical, geophysical, geological and remote-sensing data were integrated to assess the geothermal potential of study area. The results indicate that Marand holds viable shallow geothermal resources. Active tectonics—closely linked to kaolinite deposit formation of north Marand—have attracted both geoscientists and the Geoenergy sector to this area. The Zonouz kaolin deposits served as key indicators for locating potential geothermal reservoirs. Remote sensing and GIS methods were employed to detect geothermal anomalies: Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) imagery was analyzed to produce alteration maps. These maps indicate northern Marand area exhibits elevated thermal emissivity and strong potential for geothermal reservoirs.